Effect of Corn Extract and Solution of PEG to Increase Viability and Vigour of Sweet Corn Seed Deterioration at Different Incubation Periods - Herma Julendri; . Halimursyadah; . Hasanuddin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
This  study  aims  to  determine  the  combination  of  young  corn  extract  and  PEG  with  an incubation period of seed viability and vigor of the sweet corn expired. The study carried out at  the  Laboratory  of  Seed  Science  and  Technology  Faculty  of  Agriculture,  Syiah  Kuala University,  Darussalam-Banda  Aceh,  which  lasted  from  December  2012  to  July  2013. Materials used in this study is Expired sweet corn seed with 50% germination. Other materials used  are  corn  extract,  PEG  6000,  and  distilled  water.  This  research  used  Completely Randomized  Design (CRD) factorial 4 x 3,  so there are 12  combinations of treatments. Each repeated  three  times,  in  order  to  obtain  36  units  of  the  experiment.  Young  corn  extract concentration factor and solution PEG-2 bar consists of 4 levels, namely: control, 5% + - 2Ψ , 10% + - 2Ψ, and 15% + - 2Ψ. Factors incubation period consists of 3 levels : 18 hours, 24 hours,  and  30  hours.  Variables  measured  were  potential  growth,  germination,  speed  of growth,  growing  unanimity,  vigor  index  and  normal  seedling  dry  weight.  The  results  showed that the concentration of young corn extract very significant effect on the potential variables grow,  germination,  growing  simultaneity,  speed  of  growth,  vigor  index  and  normal  seedling dry  weight.  The  incubation  period  of  very  significant  effect  on  germination  variables, simultaneity  growth,  speed  of  growth  and  vigor  index.  The  incubation  period  significantly affect  the  potential  growth  and  seedling  dry  weight  normal.  There  is  a  significant  interaction between young corn extract concentration and incubation period of the vigor index variables. Control  treatment  (water)  with  an  incubation  period  of  18  hours  is  recommended  as  an alternative to improve the viability and seed vigor of sweet corn expired.